The Integration of Reason and the Heart in Islamic Epistemology: A Comparative Study of the Thoughts of Al-Ghazali and Suhrawardi - Kamila Khoirunniswatil Azkiya; Muhammad Asrori Alfa; Imron Rossidy (PT Publikasiku Academic Solution, 2026)
The debate on the position of reason and heart as sources of knowledge is one of the important issues in Islamic epistemology that is still relevant today, especially in the midst of the tendency to separate rationality and spirituality in modern scientific discourse. This research aims to analyze the position of reason and heart in the epistemology of al-Ghazali, examine the integration of conceptual knowledge and face-to-face knowledge in the philosophy of Isyraqi Suhrawardi, and formulate an integral epistemological model that is relevant to contemporary Islamic education. The research uses a qualitative approach with a literature study method, through descriptive, comparative, and interpretive analysis of al-Ghazali and Suhrawardi's primary works as well as relevant supporting literature. The results of the study show that al-Ghazali places reason as an important instrument for acquiring rational knowledge, while the purified heart becomes a means of receiving higher knowledge through kasyf, dhawq, and ma'rifat. Meanwhile, Suhrawardi developed the philosophy of Isyraqi by integrating 'ilm husuli and 'ilm hudhuri into one complete system of knowledge. The synthesis of the thoughts of the two figures produces an integral epistemological model that balances the power of reason and depth of heart. This model offers a relevant epistemological alternative to developing an Islamic education that is not only oriented to intellectual intelligence, but also to character formation and spiritual maturity.